The Influence of Tiktok Live and Beauty Influencers on Maybelline Product Purchase Decisions Among College Students - Dian Hermalia Andesta; Monica Septiani; Ade Candra (Journal of Research in Social Science and Humanities, 2025)
The purpose of this study is to determine the extent of the influence of TikTok Live and beauty influencers on the purchasing decisions of students in Bandar Lampung. The research method used is quantitative, with the sample size determined using purposive sampling as the sampling technique, resulting in 100 respondents. Data analysis techniques used validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, T tests (partial), F tests (simultaneous), and R2 tests with the help of SPSS version 31 software. The results of this study show that, partially, the TikTok Live variable (X1) has a significant effect on purchasing decisions (Y), as evidenced by a t-value of 5.149 and a significance value of 0.001 0.05. The beauty influencer variable (X2) has a significant effect on purchasing decisions (Y), as evidenced by a t-value of 5.987 and a significance value of 0.001 0.05. The results of the F test (simultaneous) show that the TikTok Live (X1) and beauty influencer (X2) variables together have a significant effect on purchasing decisions (Y) with a percentage of 78.5%, while the remaining 21.5% is explained by other factors. These results prove that the integration of TikTok Live and beauty influencers creates an effective digital marketing strategy that encourages consumers to purchase Maybelline products.